Synthesis and Study of Electrical Properties of Di Ethylene Glycol Embedded ZrO2 Films as a Gas Sensor - More, Pravin Sadashiv; Khollam, Y. B.; Gawande, S. G. (Journal of Research Updates in Polymer Science, 2013)
In this paper, the effect of Di ethylene glycol (DEG) embedded zirconium dioxide (ZrO2) on microstructure and liquid petroleum gas (LPG) sensing characteristics of ZrO2 thin films prepared by spray pyrolysis method were investigated. The films are prepared at X wt. % concentrations (X = 1, 2, 3, 4 and 5) of DEG. Microstructure of ZrO2 thin film was drastically changed by the addition of DEG, indicating that the addition of DEG was effective to prevent the agglomeration of ZrO2 particles. The high material and phase purities are found from the characterization studies in all as-prepared films. The better sensitivity factor (SF) values SF ~102 (at T = 450C) and SF = 100 (at T = 37oC) are obtained at 1 wt. % and 5 wt. % of DEG respectively. It is observed that the gas sensing characteristics of these films are strongly influenced by the optimum concentration of DEG due to the high surface area of nano-sized ZrO2 particles.